A sensor and its preparation method and application

By adding a hafnium dioxide layer to the carbon nanotube field effect transistor sensor, the problem of low sensor sensitivity and selectivity is solved, and high-sensitivity detection of copper ions is achieved, which has broad application prospects.

CN113552202BActive Publication Date: 2025-01-21CHINESE ACAD OF FISHERY SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202010338704.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-04-26
Publication Date
2025-01-21
Estimated Expiration
2040-04-26

AI Technical Summary

Technical Problem

The low selectivity and sensitivity of carbon nanotube field effect transistor sensors limit their application.

Method used

By adding a layer of hafnium dioxide, the sensitivity of the field-effect transistor sensor based on modified carbon nanotubes was increased by more than 100 times and the detection limit of copper ions was reduced to 200 pmol L-1.

Benefits of technology

The sensitivity and selectivity of the sensor are significantly improved, and the detection limit of copper ions reaches 200pmol L-1, which has broader application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113552202B_ABST
    Figure CN113552202B_ABST
Patent Text Reader

Abstract

The present application discloses a sensor and its preparation method and application. The sensor includes an insulating substrate, a hafnium oxide layer, an electrode array and a carbon nanotube layer. The insulating substrate, the hafnium dioxide layer and the electrode array are stacked and fixed in sequence. The electrode array includes a drain electrode and a source electrode. The carbon nanotube layer includes a polymer-modified carbon nanotube, and the repeating unit of the polymer contains a pyridine group. The carbon nanotube layer connects the drain electrode and the source electrode. By adding a layer of hafnium dioxide, the sensitivity of the field effect transistor sensor based on the modified carbon nanotube is increased by more than 100 times, and the detection limit (LOD) of copper ions is as low as 200pmol L ‑1 .
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a sensor and a preparation method and application thereof, belonging to the field of detection technology. Background Art

[0002] The field effect transistor based on carbon nanotubes (CNT FET) is a type of sensor with good performance and is widely used in the field of electrochemical detection. The CNT FET usually includes a substrate, an electrode and a carbon nanotube layer, wherein the electrode array includes a drain and a source, the electrode array is fixed on the substrate, and the carbon nanotube layer connects the drain and the source. When the particles to be measured gather in the carbon nanotube layer, the source and the drain are turned on, and the concentration of the particles to be measured can be determined by measuring the change in the source-drain current.

[0003] The selectivity and low sensitivity of carbon nanotube field effect transistors are both low, which limits their application. In order to improve the selectivity of carbon nanotube field effect transistors, polymers with special groups are usually used to modify carbon nanotubes, but the problem of low sensitivity of carbon nanotube field effect transistors cannot be solved. Summary of the invention

[0004] According to the first aspect of the present application, a sensor is provided. By adding a layer of hafnium dioxide, the sensitivity of the field effect transistor sensor based on modified carbon nanotubes is increased by more than 100 times, and the detection limit (LOD) of copper ions is as low as 200 pmol L -1 .

[0005] The sensor comprises an insulating substrate, a hafnium dioxide layer, an electrode array and a carbon nanotube layer. The insulating substrate, the hafnium dioxide layer and the electrode array are stacked and fixed in sequence. The electrode array comprises a drain electrode and a source electrode. The carbon nanotube layer comprises polymer-modified carbon nanotubes, wherein the repeating units of the polymer contain pyridine groups. The carbon nanotube layer connects the drain electrode and the source electrode.

[0006] In the present application, the pyridyl group refers to a group formed by pyridine losing one or more hydrogen atoms.

[0007] Optionally, the thickness of the hafnium dioxide layer is 3 to 15 nm;

[0008] Optionally, the electrode array is an interdigitated electrode;

[0009] Preferably, the thickness of the interdigitated electrode is 20 to 150 nm;

[0010] Preferably, the interdigital width of the interdigital electrode is 2 to 10 μm;

[0011] Preferably, the interdigital electrode has a finger spacing of 2 to 10 μm;

[0012] Preferably, the number of electrode pairs of the interdigitated electrodes is 25 to 50, wherein the electrode pairs include one drain electrode and one source electrode.

[0013] Furthermore, the carbon nanotube layer also includes a film-forming material;

[0014] The film-forming material is selected from at least one of chitosan, milk powder, and perfluorosulfonic acid ion exchange membrane (nafion membrane);

[0015] Preferably, the mass ratio of the film-forming material to the polymer-modified carbon nanotubes is 1:5-20.

[0016] In a specific embodiment, the polymer is poly (4-vinyl pyridine), which can non-covalently bind to carbon nanotubes and selectively bind to copper ions; in other embodiments, polymers containing pyridine groups in other repeating units can be selected as modifiers according to usage requirements.

[0017] Optionally, the carbon nanotubes may be multi-walled carbon nanotubes or single-walled carbon nanotubes, preferably single-walled carbon nanotubes;

[0018] Optionally, the electrode array is an electrode array made of gold;

[0019] Optionally, the insulating substrate is a Si / SiO2 substrate;

[0020] Preferably, the molecular weight of the poly(4-vinylpyridine) is 160,000 to 200,000.

[0021] Preferably, when detecting copper ions, the sensitivity of the sensor is 12.49 nA μmol -1 The detection limit of the sensor is 200 pmolL -1 .

[0022] A second aspect of the present application provides a method for preparing the sensor described in any one of the above items, comprising at least the following steps:

[0023] preparing a hafnium dioxide layer on an insulating substrate;

[0024] preparing an electrode array on the hafnium dioxide layer;

[0025] A carbon nanotube layer is prepared so as to connect the drain electrode and the source electrode of the electrode array.

[0026] Optionally, the step of growing a hafnium dioxide layer on an insulating substrate comprises:

[0027] A hafnium dioxide layer is prepared on the insulating substrate by atomic layer deposition.

[0028] In a specific embodiment, the insulating substrate is a Si / SiO2 substrate, and a hafnium dioxide layer is prepared on the surface of a silicon dioxide layer of the insulating substrate by atomic layer deposition.

[0029] Optionally, preparing an electrode array on the hafnium dioxide layer comprises:

[0030] Spin coating a photoresist on the hafnium dioxide layer;

[0031] Transferring the electrode array pattern to the hafnium dioxide layer by photolithography and development;

[0032] depositing a seed layer on the hafnium dioxide layer;

[0033] An electrode array is deposited on the seed layer, and the remaining photoresist is removed.

[0034] The seed layer is preferably at least one of a titanium layer, a chromium layer and a nickel layer.

[0035] Optionally, the step of preparing the carbon nanotube layer comprises:

[0036] Dispersing and centrifuging a mixed solution containing a polymer and carbon nanotubes, and taking a supernatant to obtain a polymer-modified carbon nanotube dispersion;

[0037] Mixing the polymer-modified carbon nanotube dispersion with a film-forming solution, and dripping the mixture onto the drain and source of the electrode array to form a carbon nanotube layer connecting the drain and source;

[0038] in:

[0039] The repeating unit of the polymer contains a pyridyl group;

[0040] Optionally, the mass ratio of the polymer to the carbon nanotubes is 5 to 15:1.

[0041] Optionally, the mass concentration of the polymer-modified carbon nanotube dispersion is 0.1 to 1.5%;

[0042] Optionally, the concentration of the film-forming solution is 0.5 to 1.5 mg / ml;

[0043] Optionally, the volume ratio of the polymer-modified carbon nanotube dispersion to the film-forming solution is 0.5-1.5:1.

[0044] Optionally, the solvent in the mixed solution is at least one of ethanol, deionized water, and dimethylformamide (DMF), preferably ethanol; the solvent in the film-forming solution is water, preferably deionized water; the mass ratio of carbon nanotubes to polymer in the mixed solution is 1:5-15, and the concentration of carbon nanotubes in the mixed solution is 3-8 mg / mL;

[0045] Optionally, the mixed solution containing the polymer and the carbon nanotubes is dispersed by ultrasound, the dispersion temperature is 0 to 25° C., and the dispersion time is 1 to 6 hours;

[0046] According to a third aspect of the present application, provided is the use of at least one of the sensors described in any one of the above items and the sensors prepared by the methods for preparing the sensors described in any one of the above items in detecting copper ions.

[0047] The beneficial effects of this application include:

[0048] The sensitivity of the field-effect transistor sensor based on modified carbon nanotubes was increased by more than 100 times by adding a layer of hafnium dioxide, with a detection limit (LOD) as low as 200 pmol L for copper ions. -1 .

[0049] This sensor is a very promising ion-selective sensor and has the potential to become a sensor that can be mass-produced in the future. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 The preparation method and detection mechanism of the poly (4-vinylpyridine) / single-walled carbon nanotube / hafnium oxide-field effect transistor sensor provided in Example 2;

[0051] Figure 2 The scanning electron microscope images of the micro-interdigitated electrode provided in Example 1 at different magnifications; A is a 1K magnified image, and B is a 15K magnified image;

[0052] Figure 3 An atomic force microscope image of the micro-interdigitated electrode provided in Example 1;

[0053] Figure 4 The figures are dispersion effect diagrams and electron microscope images of single-walled carbon nanotubes and poly(4-vinylpyridine)-single-walled carbon nanotube composite materials; wherein a is a picture of ethanol dispersion of single-walled carbon nanotubes, b is an electron microscope image of single-walled carbon nanotubes, c is a picture of ethanol dispersion of poly(4-vinylpyridine)-single-walled carbon nanotube composite materials, and d is an electron microscope image of poly(4-vinylpyridine)-single-walled carbon nanotube composite materials;

[0054] Figure 5 UV-visible spectra of ethanol solutions of poly(4-vinylpyridine) and poly(4-vinylpyridine)-single-walled carbon nanotubes;

[0055] Figure 6The performance test diagram of the device is provided for the comparative example; wherein A is the cyclic voltammetry curve of the micro-interdigitated electrode provided in comparative example 1 and the sensor provided in comparative example 2, B is the time-current curve of the electrode provided in comparative example 1, the sensor provided in comparative example 2 and the sensor provided in comparative example 3, and C is the linear calibration curve of the electrode provided in comparative example 1, the sensor provided in comparative example 2 and the sensor provided in comparative example 3;

[0056] Figure 7 Performance test diagram of the sensor provided in Example 2; wherein A is the cyclic voltammetry curve of the micro-interdigitated electrode provided in Comparative Example 1 and the sensor provided in Example 2, B is the time-current curve of the sensor provided in Example 2, and C is the calibration curve of the corresponding steady-state current and copper ion concentration of the sensor provided in Example 2;

[0057] Figure 8 The current-voltage curve of the sensor provided in Example 2; wherein A is the source-drain current I under different gate voltage ranges ds -V g Curve B is the corresponding source-drain current curve under different scanning gate voltages;

[0058] Fig. 9 The material / device characterization diagram provided in Example 2; wherein A is a scanning electron microscope image of the sensor provided in Example 2, B is an elemental energy spectrum diagram of the sensor provided in Example 2 before copper ion detection, C is an elemental energy spectrum diagram of the sensor provided in Example 2 after copper ion detection, and D is an ATR-FTIR spectrum of poly(4-vinylpyridine), poly(4-vinylpyridine)-single-walled carbon nanotubes, and poly(4-vinylpyridine)-single-walled carbon nanotubes-copper ion composite materials on field effect transistors, and single-walled carbon nanotubes in the figure are referred to as carbon tubes;

[0059] Fig.10 This is a graph of average current changes in response of the sensor provided in Example 2 to different metal types (≥3). DETAILED DESCRIPTION

[0060] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0061] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.

[0062] Among them, a silicon wafer with a 300nm silicon dioxide layer (resistivity 1-10Ωcm, Tianjin Semiconductor Research Institute);

[0063] Poly(4-vinylpyridine) (P4VP, Mw ≈160,000), chitosan, copper chloride (purity>98%) and phosphate buffered saline (PBS, 10 mM) were purchased from Sigma Aldrich, USA.

[0064] Single-walled carbon nanotubes (purity > 95%) were purchased from XFNANO (Nanjing, China).

[0065] All other chemicals (analytical grade) were from Tianjin Kemeier Chemical Reagent Co., Ltd. (Tianjin, China).

[0066] All deionized water used was prepared by a Milli-Q deionized water generator (Millipore, USA).

[0067] General test method:

[0068] Photolithography was performed using an MA6 UV lithography machine from Karl Suss, Germany;

[0069] SEM images were obtained using a Zeiss Supra-55 scanning electron microscope from Zeiss, Germany;

[0070] AFM images were obtained using the Dimension Icon-PT system atomic force microscope from Bruker, USA;

[0071] Attenuated total reflectance (ATR) Fourier transform infrared (FTIR) spectra were obtained by FTIR-6300 spectrometer from Jasco, Japan;

[0072] ATR-FTIR spectroscopy was used to monitor the changes on the surface of the modified electrode;

[0073] The ultraviolet-visible spectrum (UV-Vis) was tested using a Specord 210plus spectrometer from Analytik Jena, Germany;

[0074] Cyclic voltammetry (CVs) and current-time (It) curves were tested on a CHI660 electrochemical workstation provided by Shanghai Chenhua Instrument Co., Ltd.

[0075] The current-voltage (IV) curves were tested on Agilent B1500a and Cascade Summit 12000 probe stations from Agilent and Cascade, respectively.

[0076] The copper ion solutions used in the tests of the examples were all prepared by dissolving copper chloride in PBS.

[0077] Example 1 Preparation of micro-interdigitated electrodes

[0078] like Figure 1As shown, in order to ensure the insulation of the substrate, a silicon wafer with a 300nm silicon dioxide layer grown by thermal oxidation was used as the substrate. The substrate was rinsed with deionized water, dried with nitrogen, and then a 5nm hafnium dioxide layer was grown on the silicon dioxide surface by atomic layer deposition, and a photoresist (NR1500, Shipley, USA) was spin-coated on the hafnium dioxide layer. The micro-finger electrode pattern was transferred to the hafnium dioxide layer by photolithography and development. 10nm of titanium was deposited on the hafnium dioxide as a seed layer by electron beam evaporation, and a gold electrode was deposited on the titanium. After removing the excess photoresist, a micro-finger electrode was obtained, which had 30 pairs of electrode pairs and a finger spacing of 5μm.

[0079] Example 2 Preparation of poly(4-vinylpyridine) / single-walled carbon nanotube / hafnium oxide-field effect transistor sensor

[0080] Preparation of poly(4-vinylpyridine)-single-walled carbon nanotube dispersion:

[0081] 5 mg of single-walled carbon nanotubes and 50 mg of poly (4-vinyl pyridine) were added to 10 ml of ethanol and mixed to obtain a mixed solution I. The obtained mixed solution I was ultrasonically dispersed at 0°C for 1 hour to obtain a suspension. Subsequently, the suspension was centrifuged at 10000g for 30 minutes. The obtained supernatant was a poly (4-vinyl pyridine) - single-walled carbon nanotube dispersion, and the mass concentration of the poly (4-vinyl pyridine) - single-walled carbon nanotube in the dispersion was 1%.

[0082] Poly(4-vinylpyridine) / single-walled carbon nanotube / hafnium oxide-field effect transistor sensor preparation:

[0083] The field effect transistor sensor was prepared by drop casting. First, the surface of the micro-interdigital electrode was ultrasonically cleaned with deionized water and ethanol, respectively. Then, the surface was dried with nitrogen. 1 mg ml -1 The chitosan aqueous solution was mixed with the poly(4-vinylpyridine)-single-walled carbon nanotube dispersion (volume ratio 1:1) to obtain a mixed solution II. Finally, 6 microliters of the mixed solution II was dropped on the working electrode (drain and source) of the micro-interdigitated electrode provided in Example 1, and dried at room temperature for 1 hour to form a carbon nanotube layer connecting the drain and source, thereby obtaining a poly(4-vinylpyridine) / single-walled carbon nanotube / hafnium oxide-field effect transistor sensor.

[0084] Comparative Example 1 Preparation of micro-interdigitated electrodes

[0085] A silicon wafer (Si / SiO2) with a 300nm silicon dioxide layer grown by thermal oxidation was used as the substrate. The substrate was rinsed with deionized water and dried with nitrogen, and then a photoresist (NR1500, Shipley, USA) was spin-coated on the silicon dioxide. The micro-interdigitated electrode pattern was transferred to the silicon dioxide by photolithography. A 10nm titanium layer was deposited on the silicon dioxide as a seed layer by electron beam evaporation, and a gold electrode was deposited on the titanium. After stripping off the excess photoresist, the micro-interdigitated electrode was obtained.

[0086] Comparative Example 2 Preparation of poly (4-vinylpyridine) / single-walled carbon nanotube-field effect transistor sensor

[0087] Mixed solution II was prepared in the same manner as in Example 2. 6 μl of mixed solution II was dropped onto the working electrodes (drain and source) of the micro-interdigitated electrode prepared in Comparative Example 1, and dried at room temperature for 1 h to form a carbon nanotube layer connecting the drain and source, thereby obtaining a poly(4-vinylpyridine) / single-walled carbon nanotube-field effect transistor sensor.

[0088] Comparative Example 3 Preparation of single-walled carbon nanotube-field effect transistor sensor

[0089] Preparation of single-walled carbon nanotube dispersion:

[0090] 5 mg of single-walled carbon nanotubes were added to 10 ml of ethanol and mixed to obtain a mixed solution III. The obtained mixed solution III was ultrasonically dispersed at 0°C for 1 hour to obtain a suspension. Subsequently, it was centrifuged at 10000g for 30 minutes. The obtained supernatant was the single-walled carbon nanotube dispersion.

[0091] Single-walled carbon nanotube-field effect transistor sensor preparation:

[0092] The field effect transistor sensor was prepared by drop casting. First, the surface of the micro-interdigitated electrode provided in Comparative Example 1 was ultrasonically cleaned with deionized water and ethanol, respectively. Then, the surface was dried with nitrogen. -1 The chitosan aqueous solution was mixed with the above-mentioned single-walled carbon nanotube dispersion (volume ratio 1:1) to obtain a mixed solution IV. Finally, 6 microliters of the mixed solution IV was dropped on the location of the micro-interdigitated electrode working electrode (drain and source) provided in Comparative Example 1, and dried at room temperature for 1 hour to form a carbon nanotube layer connecting the drain and source, and obtain a single-walled carbon nanotube-field effect transistor sensor.

[0093] Example 3 Characterization of the Materials / Devices Obtained from Example 1 and Example 2

[0094] In the sensor obtained in Example 2, single-walled carbon nanotubes and poly (4-vinylpyridine) are used as the gate channel material and specific selection module of the sensor respectively, and the hafnium dioxide layer plays a role in signal enhancement. Figure 2This is a scanning electron microscope image of the micro-interdigitated electrode prepared in Example 1. Figure 3 The atomic force microscope image of the micro-interdigitated electrode prepared in Example 1 shows a clear interdigitated structure of the electrode in the scanning electron microscope image. Figure 3 As shown, the interdigital width and thickness of the micro-interdigital electrode are 5 μm and 75 nm, respectively. In the sensor obtained in Example 2, the poly(4-vinylpyridine)-modified single-walled carbon nanotubes form a coating on the surface of the micro-interdigital electrode working electrode. Figure 4 As shown, in the absence of poly(4-vinylpyridine), the single-walled carbon nanotubes cluster together, resulting in rapid precipitation. The poly(4-vinylpyridine)-single-walled carbon nanotube composite material is uniformly dispersed in the solution, and a single dispersed single-walled carbon nanotube can be obtained on the surface of the field effect transistor. Figure 5 It is shown that the UV-visible absorption intensity of poly(4-vinylpyridine)-single-walled carbon nanotubes is higher than that of poly(4-vinylpyridine) in the range of 300-800 nm, which also indicates that poly(4-vinylpyridine) has been combined with single-walled carbon nanotubes.

[0095] like Figure 1 As shown, copper ions can be specifically bound by the pyridine group of poly(4-vinylpyridine) and attached to the surface of single-walled carbon nanotubes. These fixed copper ions improve the charge transfer ability of poly(4-vinylpyridine) / single-walled carbon nanotube-field effect transistor sensor. Therefore, the poly(4-vinylpyridine) / single-walled carbon nanotube-field effect transistor sensor can detect the copper ion concentration according to the change of the current signal. Based on the above mechanism, the poly(4-vinylpyridine) / single-walled carbon nanotube-field effect transistor sensor can be used as a portable copper ion detector.

[0096] Example 4 Performance test of the devices provided in each example and comparative example

[0097] At room temperature, the reference voltage was set to -0.1v, and the copper ion solution was continuously added to measure the time-current curve. The data was tested by CHI 660B electrochemical workstation. The source-drain current (I ds ) was used to study the gate control effect of the device, and the data testing was completed by Agilent B1500a and Cascade Summit 12000 semi-automatic probe stations.

[0098] The cyclic voltammetry curves of the micro-interdigitated electrode provided in Comparative Example 1 and the sensor provided in Comparative Example 2 were measured, and the results were as follows: Figure 6 As shown in a and b in A; then 0.2 μmol L -1 Copper ion aqueous solution, and test the cyclic voltammetry curve of the sensor, the results are as follows Figure 6 As shown in c in A;

[0099] Depend on Figure 6 A shows that the current of the field effect transistor sensor made by poly(4-vinylpyridine)-single-walled carbon nanotube modification is 4 times that of the micro-interdigitated electrode provided in Example 1. The results show that the poly(4-vinylpyridine)-single-walled carbon nanotube composite material significantly improves the conductivity of the device. -1 After continuous addition of copper ion aqueous solution Figure 6 A pair of redox peaks can be observed in Ac, indicating that the poly(4-vinylpyridine) / single-walled carbon nanotube-field effect transistor sensor can detect copper ions.

[0100] According to the Ampere method, -0.1 V was used as the working potential to test the time-current curves of the electrode provided in Comparative Example 1, the sensor provided in Comparative Example 2, and the sensor provided in Comparative Example 3, respectively (eg Figure 6 B) and the linear calibration curve (as shown in Figure 6 C), the copper ion concentration in the copper ion aqueous solution on the device was adjusted from 0.2 μmol L -1 Increase to 1 μmol L -1 .

[0101] Figure 6 In B and C, a represents the electrode provided in Comparative Example 1, b represents the sensor provided in Comparative Example 3, and c represents the sensor provided in Comparative Example 2. Figure 6 As shown in B and C, at a copper ion concentration of 0.2 μmol L -1 to 1 μmol L -1 When the electrode provided in Comparative Example 1 and the sensor provided in Comparative Example 3 did not respond to copper ions, the sensor provided in Comparative Example 2 responded to copper ions and was linear. The calibration curve of the sensor provided in Comparative Example 2 was consistent with the copper ion concentration of 0.2 μmol L -1 to 1 μmol L -1 There is a linear relationship between them. The relative standard deviation (RSD) between sensors is 5.23%. The sensitivity of the sensor provided in Comparative Example 2 is 6.64 nA μmol -1 , with a detection limit of 20 nmol L -1 .

[0102] The same method was used to measure the cyclic voltammetry curves of the micro-interdigitated electrode provided in Comparative Example 1 and the sensor provided in Example 2. The results are as follows: Figure 7 As shown in b and a in A; then 0.02 μmol L -1 Copper ion aqueous solution, and test the cyclic voltammetry curve of the sensor, the results are as follows Figure 7 As shown in c in A;

[0103] According to the Ampere method, -0.1 V was used as the working potential to test the time-current curve of the sensor provided in Example 2 (eg Figure 7 B) and the linear calibration curve (as shown in Figure 7 C), the copper ion concentration in the copper ion aqueous solution on the device was adjusted from 0.02 μmol L -1 Increased to 0.68 μmol L -1 .

[0104] Reference Figure 6 After copper ions were added to A and 7A, the current of the sensor provided in Example 2 was five times that of the sensor provided in Comparative Example 2. In addition, the sensor provided in Example 2 was -1 The range is linearly related to the copper ion concentration, and its linear range is much larger than the sensor provided in Comparative Example 1. The bottleneck of ordinary carbon nanotube field effect sensors has been broken through in terms of detection range, giving the sensor a broader application prospect. The RSD between sensors provided in Example 2 is 1.78%, which is also lower than that of sensors without hafnium dioxide enhancement. These results show that the sensor with hafnium dioxide enhancement has better performance than the sensor provided in Comparative Example 2. The sensitivity of the sensor provided in Comparative Example 2 is 12.49nAμmol -1 , is the sensor provided in Example 1 (6.64nAμmol -1 ). As a sensor, the detection limit is one of the important parameters for evaluating whether copper ions exist in the water sample to be tested. The detection limit of the sensor after adding the hafnium dioxide layer is 200 pmol L -1 , which is 100 times that of the sensor provided in Example 1. 200 pmol L -1 (0.128 μg L -1 The detection limit of 0.128 ppb is much lower than the upper detection limit of copper ions in drinking water given by the World Health Organization (WHO) (2 ppm). In addition, compared with other studies, the detection limit in this work (200 pmol L -1 ) has obvious advantages.

[0105] In order to study the effect of poly(4-vinylpyridine) / single-walled carbon nanotube / hafnium oxide layer on the performance of the sensor, the transistor characteristics of the sensor were studied using current-voltage curves. When different gate voltages (Vg) (from -20.0 to +20.0 V (0.4 V / step), from -15.0 to +15.0 V, from -10.0 to +10.0 V, from -5.0 to +5.0 V and from -1.0 to 1.0 V) were used, the drain-source voltage (V ds ) is set to 1v. Figure 8As shown, the absolute value of the source-drain current (Ids) increases with the increase of the absolute value of the gate voltage. The increase in electron density is due to the increase in piezoelectric effect and spontaneous polarization effect. The slope of the Ids-Vg graph is positively correlated with the gate capacitance, that is, the structural correlation between the gate and the poly(4-vinylpyridine) / single-walled carbon nanotube / hafnium oxide layer. It shows that the poly(4-vinylpyridine) / single-walled carbon nanotube / hafnium oxide layer has a sensitive response to copper ions. This field effect transistor sensor has better performance than previously reported sensors and is a potential "early warning" tool for monitoring copper ions in the future.

[0106] In addition, attenuated total reflectance Fourier transform infrared spectroscopy is an effective method to evaluate the changes of poly(4-vinylpyridine) / single-walled carbon nanotube / hafnium oxide-field effect transistor sensors after adsorption of copper ions. Fig. 9 The attenuated total reflection Fourier transform infrared spectrum showed that after the copper ions were adsorbed, the peak of the pyridine ring shifted from 1595 cm -1 To 1600cm -1 The C=N energy band of poly(4-vinylpyridine) is enhanced, and this peak shift indicates that the copper ions are bound to the pyridyl group of poly(4-vinylpyridine). Fig. 9 A, 9B, and 9C are the SEM images of the sensor and the copper ions detected. From the energy spectrum image, all elements are clearly displayed on the sensor. Fig. 9 As shown, the silicon element represents the silicon dioxide substrate, the gold element is the interdigitated electrode structure, and the nitrogen and carbon represent the poly(4-vinylpyridine) and carbon nanotubes modified on the sensor. Copper is the copper ion fixed by the pyridine group of poly(4-vinylpyridine). The last one is the overall picture of the sensor after the copper ion is detected, and all the elements can be found in the picture.

[0107] Selectivity and repeatability testing of sensors

[0108] In order to verify the selectivity of this sensor, other common heavy metals (K + 、As + 、Na + 、Cd 2+ , Hg 2+ , Mn 2+ )’s current signal curve. Fig.10 1 μmol L -1 Comparison of current signals between different heavy metals. The electrical signal response of copper ions is significantly higher than that of other ions. The sensor has good selectivity and can be used as a reliable tool for rapid detection of copper ions in water.

[0109] The reusability and stability of the sensor are important parameters in the development and practical application of copper ion detection technology. The number of cycles and storage stability of the sensor were also tested. The results showed that the sensor could be cleaned more than 50 times with acetic acid and deionized water. Therefore, the cost of a single test can be as low as the same price as that of a paper-based sensor. After the sensor was sealed and stored at room temperature for 6 weeks, its sensitivity to 0.2 μmol L -1 The current response of copper ions only decreased by 5%, indicating that the sensor has long-term stability as a detection platform.

[0110] The excellent performance of the poly(4-vinylpyridine) / single-walled carbon nanotube / hafnium oxide field-effect transistor sensor can be attributed to the following aspects: first, the large surface area of ​​the carbon nanotube provides more bound poly(4-vinylpyridine) molecules, which can significantly increase the binding sites of copper ions; second, the pyridine group on poly(4-vinylpyridine) is one of the best ligands for copper ions; third, the introduction of the hafnium dioxide layer not only ensures the electronic transmission performance of the carbon nanotube, but also plays a capacitive role in reducing the sensor impedance in the circuit. These factors work together to form a stable, highly sensitive and highly selective field-effect transistor sensor.

[0111] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. Application of a field effect transistor sensor in detecting copper ions, characterized in that: The sensor comprises an insulating substrate, a hafnium dioxide layer, an electrode array and a carbon nanotube layer. The insulating substrate, the hafnium dioxide layer and the electrode array are stacked and fixed in sequence. The electrode array comprises a drain electrode and a source electrode. The carbon nanotube layer comprises polymer-modified carbon nanotubes, wherein the polymer is poly(4-vinylpyridine). The carbon nanotube layer connects the drain electrode and the source electrode.

2. The use according to claim 1, characterized in that: The thickness of the hafnium dioxide layer is 3-15 nm.

3. The use according to claim 1, characterized in that: The electrode array is an interdigitated electrode.

4. The use according to claim 3, characterized in that: The thickness of the interdigital electrodes is 20-150 nm.

5. The use according to claim 3, characterized in that: The interdigital width of the interdigital electrode is 2-10 μm.

6. The use according to claim 3, characterized in that: The interdigital electrode has an interdigital spacing of 2 to 10 μm.

7. The use according to claim 3, characterized in that: The number of electrode pairs of the interdigitated electrodes is 25-50, wherein the electrode pairs include a drain electrode and a source electrode.

8. The use according to claim 1, characterized in that: The carbon nanotube layer also includes a film-forming substance; The membrane-forming material is selected from at least one of chitosan, milk powder and perfluorosulfonic acid ion exchange membrane.

9. The use according to claim 8, characterized in that: The mass ratio of the film-forming material to the polymer-modified carbon nanotubes is 1:5-20.

10. The use according to claim 1, characterized in that: The carbon nanotubes are single-walled carbon nanotubes; The electrode array is an electrode array made of gold; The insulating substrate is a Si / SiO2 substrate.

11. The use according to claim 10, characterized in that: The molecular weight of the poly(4-vinylpyridine) is 160,000-200,000.

12. The use according to claim 1, characterized in that: When detecting copper ions, the sensitivity of the sensor was 12.49 nAμmol -1 The detection limit of the sensor is 200 pmol L -1 .

13. The use according to any one of claims 1 to 12, characterized in that: At least the following steps are included: preparing a hafnium dioxide layer on an insulating substrate; preparing an electrode array on the hafnium dioxide layer; A carbon nanotube layer is prepared so as to connect the drain electrode and the source electrode of the electrode array.

14. The use according to claim 13, characterized in that The step of growing a hafnium dioxide layer on an insulating substrate comprises: A hafnium dioxide layer is prepared on the insulating substrate by atomic layer deposition.

15. The use according to claim 13, characterized in that: The step of preparing an electrode array on the hafnium dioxide layer comprises: Spin coating a photoresist on the hafnium dioxide layer; Transferring the electrode array pattern to the hafnium dioxide layer by photolithography and development; depositing a seed layer on the hafnium dioxide layer; An electrode array is deposited on the seed layer, and the remaining photoresist is removed.

16. The use according to claim 13, characterized in that: The method for preparing the carbon nanotube layer comprises: Dispersing and centrifuging a mixed solution containing a polymer and carbon nanotubes, and taking a supernatant to obtain a polymer-modified carbon nanotube dispersion; Mixing the polymer-modified carbon nanotube dispersion with a film-forming solution, and dripping the mixture onto the drain and source of the electrode array to form a carbon nanotube layer connecting the drain and source; in: The polymer contains a pyridyl group in the repeating unit.

17. The use according to claim 16, characterized in that The mass concentration of the polymer-modified carbon nanotube dispersion is 0.1-1.5%.

18. The use according to claim 16, characterized in that The concentration of the film-forming solution is 0.5-1.5 mg / mL -1 .

19. The use according to claim 16, characterized in that: The volume ratio of the polymer-modified carbon nanotube dispersion to the film-forming solution is 0.5-1.5:1.

Citation Information

Patent Citations

  • Electrically-driven organic color-center-based single-photon sources and sensors

    US20200013991A1

  • Chemical sensor

    WO2016145300A1